ASPECTS REGARDING THE POSSIBLE DISCRETIONARY POWER OF THE PRESIDENT OF ROMANIA IN EXERCISING THE POWER TO PROMULGATE LAWS - Oana ŞARAMET (Bulletin of the Transilvania University of Braşov Series VII: Social Sciences • Law • Vol. 17(66) No. 2 - 2024, 2024)
The Constitution of Romania, republished, provides, in art. 1 paragraph (4), that the organization and functioning of our state is based on the principle of separation and balance of powers in the state. The true functioning of this principle is conditioned by the configuration of control mechanisms and mutual collaboration, especially between the most important exponents of these powers, such as the Parliament and the President of Romania. One of the powers exercised by the President of Romania in his relations with Parliament is the promulgation of laws. Through this article we aim to analyze whether this is a genuine attribution, as well as whether it can be exercised at the discretion of the head of state.
Keywords: President of Romania; promulgation; balance of powers; discretionary power; Parliament.